Closed-end funds and discount control mechanisms - Roman Kräussl; Joshua M. Pollet; Denitsa Stefanova (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
The discount control mechanisms that closed-end funds often choose to adopt before IPO are supposedly implemented to narrow the difference between share price and net asset value, We find evidence that non-discretionary discount control mechanisms such as mandatory continuation votes serve as costly signals of information to reveal higher fund quality to investors, Rents of the skill signaled through the announcement of such policies accrue to managers rather than investors as differences in skill are revealed through growing assets under management rather than risk-adjusted performance.
urn:nbn:de:hebis:30:3-691288
Keywords: G10; G23; 330; Closed-end funds; discount; performance; skill; signaling; information asymmetry; repurchases; continuation vote; Closed-end funds